What is religion?: The unexplained subject matter of religious studies - Bergunder, Michael (Method & theory in the study of religion, 2014)
Religious studies cannot agree on a common definition of its subject matter. To break the impasse, important insights from recent discussions about post-foundational political theory might be of some help. However, they can only be of benefit in conversations about “religion” when the previous debate on the subject matter of religious studies is framed slightly differently. This is done in the first part of the article. It is, then, shown on closer inspection of past discussions on “religion” that a consensus-capable, contemporary, everyday understanding of “religion,” here called Religion 2, is assumed, though it remains unexplained and unreflected upon. The second part of the article shows how Religion 2 can be newly conceptualized through the lens of Ernesto Laclau’s political theory, combined with concepts from Judith Butler and Michel Foucault, and how Religion 2 can be established as the historical subject matter of religious studies. Though concrete historical reconstructions of Religion 2 always remain contested, I argue that this does not prevent it from being generally accepted as the subject matter of religious studies. The third part discusses the previous findings in the light of postcolonial concerns about potential Eurocentrism in the concept of “religion.” It is argued that Religion 2 has to be understood in a fully global perspective, and, as a consequence, more research on the global religious history of the 19th and 20th centuries is urgently needed.